Boron-containing radiator coatings of ionization chambers of neutron flux detection sensors - Petr B. Baskov; Boris S. Salamakha; Yakov V. Glazyuk; Artur A. Namakshinas; Sergey A. Bondarenko; Ilya M. Mushin; Alexander S. Khudin (Nuclear Energy and Technology)
The proposed solution for the production of new boron-containing radiator materials – composite coatings with neutron conversion material (10B isotope) – for ionization chambers electrodes is based on the technology of chemical and structural modification of the surface using heat-resistant oxide materials (silicon and boron oxides). The paper presents the results of the development of a neutron-sensitive radiator material based on an oxide micro-dimensional composite coating consisting of an intermediate adhesive layer of silicon dioxide (SiO2) and a neutron-sensitive functional layer of boric anhydride (B2O3). The technological basis consists of the sequential processes of thermal destruction of polyorganosiloxane of the PES-5 brand and pyrolytic decomposition of boric acid (H3BO3). Studies using infrared and fiber-optic interferometric spectroscopy have shown that during the formation of a silicon dioxide layer, an amorphous silicate of a linear chain structure with a developed surface is formed, which contributes to the subsequent formation of a functional boric anhydride layer. The specific neutron sensitivity of boron-containing radiator coatings was measured by alpha spectrometry. It was found that at a surface density of boric anhydride of 2.5 mg/cm2, the specific neutron sensitivity is of the order of 3∙10-18Coulomb/neutron. It is shown that the boron-containing radiator coating retains its integrity and nuclear physical properties during thermocyclic tests (4 cycles at 600 °C). The boron-containing radiator coating is characterized by high adhesion properties to the metallic surface of the electrodes (grade 321 steel) of the ionization chamber. The composite coating is resistant to vibration when exposed to high-frequency (200 Hz) and low-frequency (6–35 Hz) vibration loads.